PENERAPAN HUKUM MORTALITA MAKEHAM UNTUK PENENTUAN NILAI CADANGAN PREMI ASURANSI JOINT LIFE DENGAN METODE FACKLER - JANNAH, MIFTAAHUL; SUPRIATNA, AGUS; RIAMAN, RIAMAN (E-Jurnal Matematika; Vol 9 No 3 (2020)DO - 10.24843/MTK.2020.v09.i03.p297, 2020)
Joint life insurance is life insurance with an amount of more than one person, where the benefits are paid when one of the insured dies. The possibility of insurance companies will suffer losses if the claims that occur are more than predicted, so the premium reserve calculation is required. In this study, reserves were calculated using the Fackler method based on the Indonesian Mortality Table 2011 and the Makeham Assumption Mortality Table. The Indonesian Mortality Table 2011 was analyzed for the estimated parameters contained in the Makeham Assumption Mortality Table. Then the premium calculation and premium reserve calculation are done using the Fackler method based on the Makeham Assumption Mortality Table and the comparison uses the Indonesian Mortality Table 2011. The results of the calculation of the premiums based on the Makeham Assumption Mortality Table are greater than using the Indonesia Mortality Table 2011, while the premium reserve results are greater using the Indonesian Mortality Table 2011 than using the Makeham Assumption Mortality Table. This is because the chances of survival based on the Makeham Assumption Mortality Table are smaller than the Indonesian Mortality Table 2011.